Coexistence networks of soil methanogens are closely tied to methane generation in wetlands on the northeastern of the Qinghai–Tibet Plateau - He, Kun; Zhao, Jiacheng; Pan, Jianbin; Zhang, Qi; Feng, Huyuan (Frontiers in Microbiology, 2025)
Wetlands are the largest natural sources of methane (CH4) emissions worldwide, with methanogenic archaea serving as the primary drivers of CH4 production. Nevertheless, the influences of biotic factors (e.g., methanogen abundance, community diversity and composition) and abiotic factors (e.g., soil properties) on potential CH4 production rates remain insufficiently understood in Qinghai-Tibet Plateau. In this study, we examined soil properties, potential methane production rates (PMPRs), methanogenic archaeal abundance, diversity, community structure, and co-occurrence networks across four wetlands (two desert wetlands and two peatlands) with contrasting soil conditions on the northeastern edge of the Qinghai-Tibet Plateau. We found no significant differences in methanogen abundance and PMPRs among the four wetlands, but the two were significantly positively correlated. The structure of methanogenic communities varied markedly among wetlands and was mainly shaped by soil pH. The complexity of co-occurrence networks was positively correlated with both methanogen diversity and PMPRs. Further analysis using partial least squares path modeling (PLS-PM) revealed that PMPRs were closely associated with soil nutrition (soil total organic carbon and total nitrogen; standardized path coefficient = 0.307), methanogenic abundance (0.570) and network complexity (0.238). It indicated that biotic factors may exert a greater influence than abiotic factors on soil PMPRs in wetland ecosystems. Additionally, complex microbial interaction networks may play a more crucial role in regulating PMPRs than methanogenic diversity and community structure. Our study highlights a strong link between methanogenic network complexity and methane-producing potential, offering a novel perspective on the relationship between community interactions and ecosystem function.